Biomechanical study of the abductor pollicis longus & extensor pollicis brevis after release and reconstruction of the first dorsal compartment of the wrist. (October 2021) - Gupta, Amit; Mirzaee, Fateme; Farahanchi Baradaran, Amir; Aslani, Mohammad Amin; Aslani, Hamidreza
Abstract: Background: The purpose of this study was to determine the biomechanical changes after first dorsal compartment release and after Z-plasty of the first dorsal compartment with respect to the excursion and displacement of the abductor pollicis longus and extensor pollicis brevis tendons. Materials and methods: Six fresh frozen cadaveric hand and forearms were obtained and the tendons of the abductor were exposed and separated from surrounding tissues through a palmar incision and tenotomized at the musculotendinous junction. The excursion and displacement of the abductor pollicis brevis and flexor pollicis brevis tendons were measured for all six cadaveric hands. Results: Increases in tendon excursion were observed in both the abductor pollicis longus (29%) and extensor pollicis brevis (30%) while these observations after Z-plasty were 0.04% for abductor pollicis longus and 0.07% for extensor pollicis brevis. With the use of the modified Elftman curve for the Lengths, tension relationship and Brand's data for resting fiber length we found that 1 cm increase of The excursion of the APL and EPB will decrease tension %65 and %80 respectively. There was also a 12.2-mm displacement of the tendons after release and 4.8 mm displacement after z-plasty of the compartment. Conclusion: It seems that Procedures such as enlargement plasty of Kapandji or Z-plasty will increase the size of the compartment but will not change the biomechanical behaviors of the tendons significantly. Highlights: One of the common causes of wrist and hand pain or disability is the first extensor compartment entrapment. Surgical approaches for de Quervain tenosynovitis may lead to volar subluxation or excursion of the APL and EPB tendons. The purpose of this study was to determine the biomechanical changes after first dorsal compartment release.